Heavy and super-heavy nuclei and elements : production and properties: Editorial preface to the topical collection - Alamanos, N.; Borge, M. J.G.; Hofmann, S.; Möller, P.; Popeko, A. G. (European Physical Journal A, 2025)
The advances in understanding and producing heavy and super-heavy elements is the subject of this topical collection. The main covered subjects are: the description of the theory, developments of super-heavies and the determination of the Island of Stability as well as the role of these nuclei as part of the r-process scenario. The accurate determination of reaction processes are crucial to enable advances in the production of the heaviest elements. A short summary of the achievements at some of the facilities, their improved spectrometers and recent spectroscopy results complete this topical collection.